Targeted Methylation of the LncRNA NEAT1 Suppresses Malignancy of Renal Cell Carcinoma - Chen, Jieqing; Liao, Xinhui; Cheng, Jianli; Su, Ganglin; Yuan, Fen; Zhang, Zhongfu; Wu, Jianting; Mei, Hongbing; Tan, Wanlong (Frontiers in Cell and Developmental Biology, 2021)
Long-chain non-coding RNA (LncRNA) has been found to play an important role in the regulation of the occurrence and progression of renal cell carcinoma (RCC). In this study, we demonstrated that LncRNA NEAT1 expression and m6A methylation level was decreased in RCC tissues. Furthermore, we found that the downregulated expression level of LncRNA NEAT1 was a prognostic indicator for patients with RCC. Then we used CRIPSR/dCas13b-METTL3 to methylate LncRNA NEAT1 in 786-O and OSRC RCC cells. We found the expression levels of LncRNA NEAT1 were upregulated after methylated by dCas13b-METTL3 in 786-O and OSRC RCC cell. And the proliferation and migration ability of RCC cells was decreased after methylated LncRNA NEAT1. Finally, we examined the effect of LncRNA NEAT1 hypermethylation on the transcriptome. We found differentially expressed genes in RCC cells were associated with “cGMP-PKG signaling pathway”, “Cell adhesion molecules” and “Pathways in cancer”. In conclusion, CRISPR/Cas13b-METTL3 targeting LncRNA NEAT1 m6A methylation activates LncRNA NEAT1 expression and might provide a new light on the treatment for RCC